Library buildings : preparations for planning - Dewe, Michael; International Federation of Library Associations and Institutions; College of Librarianship Wales (München ; New York : K.G. Saur, 1989)
This book reveals how to plan any kind of library building
Eighth Seminar on Library Buildings was organised by the IFLA Section on Library Buildings and Equipment in conjunction with the College of Librarianship Wales.
Proceedings of the seminar held in Aberystwyth, August 10 - 14, 1987.
Includes bibliographical references
MF23/01/2019
Loans
Keywords: Library architecture; Library buildings; Library building - design and construction